2018
DOI: 10.1002/lary.27684
|View full text |Cite
|
Sign up to set email alerts
|

Voice outcomes following medialization laryngoplasty with and without arytenoid adduction

Abstract: Objective Voice outcomes following medialization laryngoplasty (ML) for unilateral vocal fold paralysis (UVFP) were compared to those who underwent ML plus arytenoid adduction (AA) (ML+AA). Methods Single institution retrospective review of patients with UVFP undergoing ML and ML+AA (2009–2017). Demographic information and history of laryngeal procedures were collected. Preoperative and postoperative Voice Handicap Index‐10 (VHI‐10) and Consensus Perceptual Auditory Evaluation of Voice (CAPE‐V) were assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
1
10
0
2
Order By: Relevance
“…16,17 Other studies have suggested improved outcomes when arytenoid adduction is added to thyroplasty, although patients who required arytenoid adduction had poorer voice outcomes preoperatively. 18 Swallow outcomes also improve after thyroplasty, with or without arytenoid adduction. 19 As noted earlier, anatomic reduction the glottic gap can reduce the risk of aspiration.…”
Section: Dysphoniamentioning
confidence: 98%
“…16,17 Other studies have suggested improved outcomes when arytenoid adduction is added to thyroplasty, although patients who required arytenoid adduction had poorer voice outcomes preoperatively. 18 Swallow outcomes also improve after thyroplasty, with or without arytenoid adduction. 19 As noted earlier, anatomic reduction the glottic gap can reduce the risk of aspiration.…”
Section: Dysphoniamentioning
confidence: 98%
“…The present author has developed the “titanium medialization laryngoplasty implant” (TMLI) (patent number in Japan: 6434921) and reported on its usability 7 . Further, a number of modifications to AA, along with the surgical indications, have also been reported 8–11 . The present author also developed and proved the clinical utility of the “all muscles preserved method” (AMPM) 12 …”
Section: Introductionmentioning
confidence: 80%
“…7 Further, a number of modifications to AA, along with the surgical indications, have also been reported. [8][9][10][11] The present author also developed and proved the clinical utility of the "all muscles preserved method" (AMPM). 12 This study aims to present and discuss the results associated with a combined surgical approach of the above-mentioned methods to treat patients with severe breathy hoarseness.…”
Section: Introductionmentioning
confidence: 83%
“…AA plays a part in UVCP treatment by directly stretching arytenoid cartilage directly. AA is usually adjuvant medialization procedures (46)(47)(48). A novel endoscopic AA with IL was developed as a rapid, minimally invasive solution for UVFP (49).…”
Section: Type I Thyroplasty and Aamentioning
confidence: 99%